Fluorescence Spectroscopy of Interaction between Hg(II) and Keyhole Limpet Hemocyanin - Fan, Yulan; Zeng, Guidi; Chen, Huifang; Wu, Yongquan; Xue, Jun; Li, Xun (Asian Journal of Chemistry, 2015)
The interaction between Hg(II) and keyhole limpet hemocyanin (KLH) under simulated physiological conditions was investigated by fluorescence spectroscopy. The keyhole limpet hemocyanin fluorescence quenching mechanism and the interacting mode of the Hg(II)-KLH system were studied. The experimental data showed that the intrinsic fluorescence of keyhole limpet hemocyanin was quenched with Hg(II) through a static quenching process, which indicates that a Hg(II)-KLH complex was formed. The thermodynamic parameters, binding constants and number of binding sites were calculated at different temperatures. These experimental results show that the hydrogen bonds and van der Waals forces are attributed to stabilization of the Hg(II)-KLH system. Synchronous fluorescence spectra indicated that Hg2+ lead to conformational changes of keyhole limpet hemocyanin.